Business process management is a work in progress - Schick, Shane (Computing Canada, 2006)
Savas Ozatalay, dean of the School of Business at Widener University in Wilmington, Del., was on stage at ProcessWorld 2006 to announce the launch of Widener's Master's in Business Process Management, which, along with other programs, is designed to arm the workforce with the kind of managers needed to lead these sorts of projects. Although schools such as Widener already offer a Master's in Information Systems with a processing innovation component, Ozatalay said that program is aimed more at "CIOs to be." The Master's in BPM, on the other hand, is aimed at someone else, though it's hard to say whom, exactly. In fact, ProcessWorld distinguished itself by presenting an unusual blend of IT department staff with change management consultants, efficiency experts and other exiles from the business side who suddenly found themselves talking about technology.